"Benign" monoclonal IgE gammopathy. Issue 6239 (23rd August 1980) - Ludwig, H; Vormittag, W
Abstract : So far IgE monoclonal paraproteins have been found only in patients with malignant diseases, though there are benign monoclonal paraproteins of other immunoglobulin classes. A patient with osteoporosis first seen in Paris in 1965 was found to have a paraprotein type lambda. In 1977 immunoelectrophoresis identified this as IgE lambda paraprotein, and immunodiffusion studies showed precipitin bands identical with those in patients with IgE myeloma. This patient seemed to have a benign monoclonal IgE gammopathy which had existed for 14 years. Though the possibility of transition into multiple myeloma cannot be excluded, this case suggests that a monoclonal expansion of IgE lymphocytes need not produce malignant change.